Ethnicity in history: Some research problems and possibilities - Heršak, Emil (1998)
The paper presents some problems in the historical study of ethnic development. The concrete task re-lates to an analysis of the historical phases in the development of the Croatian ethnie. The problems of historical discontinuity/continuity, required language skills, terminological analysis and objective and subject approaches to the theme are briefly treated.
Projekt MZOS
ENG